Acute tubulointerstitial nephritis complicating Legionnaires' disease: a case report - Daumas Aurélie (Journal of Medical Case Reports, 2012)
Abstract Introduction Legionnaires' disease is recognized as a multi-systemic illness. Afflicted patients may have pulmonary, renal, gastrointestinal tract and central nervous system complications. However, renal insufficiency is uncommon. The spectrum of renal involvement may range from a mild and transient elevation of serum creatinine levels to anuric renal failure requiring dialysis and may be linked to several causes. In our present case report, we would like to draw attention to the importance of the pathological documentation of acute renal failure by reporting a case of a patient with acute tubulointerstitial nephritis complicating Legionnaires' disease. Case presentation A 55-year-old Caucasian man was admitted to our hospital for community-acquired pneumonia complicated by acute renal failure. Legionella pneumophila serogroup type 1 was diagnosed. Although the patient's respiratory illness responded to intravenous erythromycin and ofloxacin therapy, his renal failure worsened, he became anuric, and hemodialysis was started. A renal biopsy was performed, which revealed severe tubulointerstitial nephritis. After initiation of steroid therapy, his renal function improved dramatically. Conclusions This case highlights the importance of kidney biopsies in cases where acute renal failure is a complicating factor in Legionnaires' disease. If the presence of acute tubulointerstitial nephritis can be confirmed, it will likely respond favorably to steroidal treatment and thus irreversible renal damage and chronic renal failure will be avoided.